Biomass steam gasification in bubbling fluidized bed for higher-H2 syngas: CFD simulation with coarse grain model. (8th March 2019) - Qi, Tian; Lei, Tingzhou; Yan, Beibei; Chen, Guanyi; Li, Zhongshan; Fatehi, Hesameddin; Wang, Zhiwei; Bai, Xue-Song
Abstract: A comprehensive coarse grain model (CGM) is applied to simulation of biomass steam gasification in bubbling fluidized bed reactor. The CGM was evaluated by comparing the hydrodynamic behavior and heat transfer prediction with the results predicted using the discrete element method (DEM) and experimental data in a lab-scale fluidized bed furnace. CGM shows good performance and the computational time is significantly shorter than the DEM approach. The CGM is used to study the effects of different operating temperature and steam/biomass (S/B) ratio on the gasification process and product gas composition. The results show that higher temperature enhances the production of CO, and higher S/B ratio improves the production of H2, while it suppresses the production of CO. For the main product H2, the minimum relative error of CGM in comparison with experiment is 1%, the maximum relative error is less than 4%. For the total gas yield and H2 gas yield, the maximum relative errors are less than 7%. The predicted concentration of different product gases is in good agreement with experimental data. CGM is shown to provide reliable prediction of the gasification process in fluidized bed furnace with considerably reduced computational time. Highlights: Computational time of Coarse Grain Method significantly shorter than that of Discrete Element Method. In simulation of biomass gasification, maximal relative error of H2 predicted by CGM is less than 4%. Higher gasification temperature in favor of production of CO. Higher gasification steam/biomass ratio in favor of production of H2 .